Technology use to support employment-related outcomes for people with intellectual and developmental disability: an updated meta-analysis - Damianidou, Despoina; Arthur-Kelly, Michael; Lyons, Gordon; Wehmeyer, Michael L. (International journal of developmental disabilities, 2019)
The aim of this study is to update and extend an original meta-analysis which included papers published up to and including 2003 and investigated the impact of technology use on employment-related outcomes for people with intellectual and developmental disability. Following on from the original meta-analysis, this study is a meta-analysis of pertinent single-subject experimental design studies conducted from 2004 to 2016 and employs the same metric methods as the original contribution. The results are generally consistent with those of the original meta-analysis, namely, applied cognitive technology effectively supports employment-related outcomes for people with intellectual and developmental disability. Nevertheless, significant differences in the intervention effects were found (a) between groups of individuals with varying levels of disability, and (b) between interventions utilizing technology with and without universal design features. In line with the original contribution, applied cognitive technology seems to support people with intellectual and developmental disabilities to better achieve employment-related outcomes. More research is needed though to explore the impact of different types of technology on employment-related outcomes.